The Role of Long Non-Coding RNAs in the Tumor Immune Microenvironment - Guo, Yingli; Xie, Yajuan; Luo, Yao (Frontiers in Immunology, 2022)
Tumorigenesis is a complicated process caused by successive genetic and epigenetic alterations. The past decades demonstrated that the immune system affects tumorigenesis, tumor progression, and metastasis. Although increasing immunotherapies are revealed, only a tiny proportion of them are effective. Long non-coding RNAs (lncRNAs) are a class of single-stranded RNA molecules larger than 200 nucleotides and are essential in the molecular network of oncology and immunology. Increasing researches have focused on the connection between lncRNAs and cancer immunotherapy. However, the in-depth mechanisms are still elusive. In this review, we outline the latest studies on the functions of lncRNAs in the tumor immune microenvironment. Via participating in various biological processes such as neutrophil recruitment, macrophage polarization, NK cells cytotoxicity, and T cells functions, lncRNAs regulate tumorigenesis, tumor invasion, epithelial-mesenchymal transition (EMT), and angiogenesis. In addition, we reviewed the current understanding of the relevant strategies for targeting lncRNAs. LncRNAs-based therapeutics may represent promising approaches in serving as prognostic biomarkers or potential therapeutic targets in cancer, providing ideas for future research and clinical application on cancer diagnosis and therapies.